Predictors of Unintended Pregnancy among Indian women: An analysis from NFHS-IV Survey - Kishun, Jai; Chandra, Abhishek; Kumar, Anup; Singh, Uttam (Insights in Public Health Journal, 2025)
Abstract Background Low levels of women’s decision-making over control of sexual intercourse, contraceptive use, domestic violence with intimate partners not only have impact on socioeconomic and cultural aspects but also on unintended pregnancies. Which create serious public health issues associated with physical, reproductive and mental health consequences. Objectives The aim of this study was to explore the predictors of unintended pregnancy among socio-demographic factors, contraceptive use, family planning methods, media exposure etc. among Indian women. State-wise prevalence of unintended pregnancies was also investigated to see which states need more attention Methods A total of 32428 married women aged between 15-49 years, who responded on current pregnancy wanted were observed in NFHS-IV (2015-16) survey data. Out of these, 3,842 were found eligible for this study. Logistic regressions were used for analysis using SPSS23 software. Results The mean age of 3,842 women respondents was 25.27 ± 4.97 years. 12.3% of them were unintended pregnancies. Women aged between 25-34 years (OR = 1.21, 95% CI: 0.99-1.48) and 35-49 years (OR = 1.50, 95% CI: 1.02-2.21) were more likely to have an unintended pregnancy than 15–24 years. Working women were 7% (OR = 0.93, 95% CI: 0.73-1.18) less likely to have an unintended pregnancy than not working. Women who never used contraception were 1.4 times more likely to have an unintended pregnancy. Conclusions Sociodemographic disparities need to be addressed to promote reproductive health and welfare services. Preventing physical violence by intimate partners against women could reduce unintended pregnancy. Key messages Improving women’s status through educational and occupational initiatives could contribute to reducing physical violence and the incidence of unintended pregnancies Keywords: Unintended Pregnancy, Women, NFHS-IV, India